(untitled) - Madlenakova, Lucia (Doprava a spoje, 2011)
The paper deals with establishing a methodology for evaluating offers postal services and establish the optimal product portfolio of postal services. The optimum range of postal services based on an appreciation of the requirements and preferences of individual subject categories postal market: customer - provider - expert.